Decreasing prevalence of HCV coinfection in all risk groups for HIV infection between 2004 and 2011 in Spain. Issue 5 (3rd November 2014) - Serrano‐Villar, S.; Sobrino‐Vegas, P.; Monge, S.; Dronda, F.; Hernando, A.; Montero, M.; Viciana, P.; Clotet, B.; Pineda, J. A.; del Amo, J.; Moreno, S.; CoRIS
Summary While hepatitis C virus (HCV) infection seems to be expanding among HIV‐infected men who have sex with men (MSM), the rate of coinfection in intravenous drug users (IDU) is assumed to remain constant. We evaluated the serial prevalence of HIV/HCV coinfection across all risk groups for HIV infection in Spain. We used data from 7045 subjects included in the multicentre, prospective Spanish Cohort of Adult HIV‐infected Patients (CoRIS) between 2004 and 2011. We analysed risk factors for HIV/HCV coinfection by logistic regression analyses. The prevalence of HIV/HCV coinfection decreased from 25.3% (95% CI, 23.1–27.5) in 2004–2005 to 8.2% (95% CI, 6.9–9.5) in 2010–2011. This trend was consistently observed from 2004 to 2011 among all risk groups: IDU, 92.4% to 81.4%; MSM, 4.7% to 2.6%; heterosexual men, 13.0–8.9%; and heterosexual women, 14.5–4.0% (all P < 0.05). Strongest risk factors for HIV/HCV coinfection were IDU (OR, 54.9; 95% CI, 39.4–76.4), birth decade 1961–1970 (OR, 2.1; 95% CI, 1.1–3.7) and low educational level (OR, 2.4; 95% CI, 1.6–3.5). Hence, the prevalence of HIV/HCV coinfection decreased in Spain between 2004 and 2011. This decline was observed across all risk groups and is likely to be explained by a declining burden of HCV in the general population.